Nusantara Islam and Nusantara Christianity: Criticizing The Theology of Violence and Peace In Religious Relations In Indonesia - Pandiangan, Pangihutan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Violence has become a daily human problem, in every aspect of life. Even violence has become a culture, which is the result of human creation. Humans create violence to fulfill their desires. The debate about the relevance of religion and violence as well as peace has seen a rapid increase since the turn of the century. This is due to globalization which has brought interaction between various nations and civilizations, including Indonesia. The result of these changes is increased awareness of peace and security, and in turn, increased conflict and violence in almost all regions of Indonesia. For example, the rejection of the construction of places of worship and also the way of looking at religion by placing religion as a source of conflict, has given rise to various attempts to reinterpret religious teachings and then find common ground at a certain level in the hope that violence and conflict between religious communities will be reduced if the adherents of each religion tolerant. Elimination of blind fanaticism, religious education from an early age, having and cultivating an attitude of nationalism and dialogue between religious and cultural communities are also needed. Eliminate the defensive apologetic attitude and approach it through a non-apologetic attitude. As well as returning to local noble values that are rooted in Islam and Christianity from the beginning of the archipelago.